Determinación de el antígeno prostático específico mediante las pruebas inmunocromatográficas y de Elisa en los integrantes mayores de 40 años del Batallón de infantería BI 21 Macará en el periodo de junio a noviembre del 2013. - Calle Suárez, Sandy Mariana (2013)
Prostate abnormalities are consider as a very common problem in older man, although every day more cases are found in young men; it is estimated that two out of three men over 40 years, suffer from prostate ailments and the number increases as age increases, due to this situation as prophylactic measure the recommendation worldwide is to get tested for serum PSA from 40 years of age for those with two or more first-degree relatives of consanguinity diagnosed with any prostatic alteration especially, when it comes to prostate cancer. The inmunochromatograpic method is a test that meets the characteristics necessary to be used as screening of prostate cancer. It is simple, quick, inexpensive, minimally invasive and has a good efficacy. However, a positive result implies the need for a quantitative measurement. The ELISA method is a quick, noninvasive test. Is the most sensitive for an early detection of any rostatic alteration, as to obtain a value higher than normal total PSA it is presumed that the patient already has cancer but there is also the probability that it is a benign pathology. In the Institution of Batallon de Infanteria BI 21 Macara, the members suffer lack of information about the topic, being the reason why they haven't done a test of Prostate-Specific Antigen by any method, so the present research work is aimed at the realization of a qualitative and quantitative analysis in male persons over 40 years old For the analysis we considered to all people of this institution who meet the inclusion criteria. Samples were collected in September 2013, then analyzed and processed by ELISA method and Immunochromatography. Once the analysis were performed in the studied population using the two methods Immunochromatographic and ELISA, the results obtained from the 65 samples correspondent to 100% were within the values considered normal.